2019
DOI: 10.18039/ajesi.577234
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Academic Entitlement Questionnaire

Abstract: Academic entitlement is one of the most significant problems that affect not only students' academic success but also lead them to engage in various uncivil and undesired behaviors such as disrespect, anger and aggression. It might disrupt individuals' psychological and social adaptation by itself or interacting with other problems. Academically entitled students are inconsiderate of their friends, intolerant to even constructive feedback, and exhibit unethical behaviors such as cheating, plagiarism, etc.. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…The university students believe that there is favoritism in the universities, and favoritism is more common than any other form of corruption such as bribery, fraud and embezzlement (Julián and Bonavia, 2020;Walters et al, 2019). The students may expect privileges from the faculty members (Achacoso, 2002) as they focus on performance and have the tendency to keep their grades up (Kurtyilmaz, 2019). In the domestic literature, no studies are encountered regarding student favoritism in Turkish universities.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The university students believe that there is favoritism in the universities, and favoritism is more common than any other form of corruption such as bribery, fraud and embezzlement (Julián and Bonavia, 2020;Walters et al, 2019). The students may expect privileges from the faculty members (Achacoso, 2002) as they focus on performance and have the tendency to keep their grades up (Kurtyilmaz, 2019). In the domestic literature, no studies are encountered regarding student favoritism in Turkish universities.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Üniversite öğrencileri, üniversitelerde kayırmacılık olduğuna ve kayırmacılığın rüşvet, dolandırıcılık ve zimmete para geçirme gibi diğer yolsuzluk türlerinden daha yaygın olduğuna inanmaktadırlar (Julián ve Bonavia, 2020;Walters ve diğ., 2019). Öğrenciler, performansa (edime) odaklandıkları ve notlarını yüksek tutma eğiliminde oldukları (Kurtyilmaz, 2019) için öğretim üyelerinden ayrıcalık bekleyebilmektedirler (Achacoso, 2002). Ulusal alanyazında, Türk üniversitelerinde öğrenci kayırmacılığı ile ilgili herhangi bir çalışmaya rastlanmamıştır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Goodboy and Frisby (2014) concluded that students with high academic entitlement engage in negative, undesirable behaviours and are highly critical of others. Kurtyilmaz (2019) reported that entitlement promotes undesirable behaviours among students in academic situations, such as anger, disrespect, and aggression. Elias (2017) found a positive correlation between academic entitlement and exam cheating.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Chowning and Campbell (2009) claimed that entitlement most affects university students. (Kurtyilmaz, 2019) believes that academic entitlement among university students may lead to students engaging in unethical and unacceptable behaviours such as aggression, disrespect, intolerance, and cheating. In the same context, (Campbell et al, 2004) added that academic entitlement among university students leads to negative effects that appear in the form of negative behaviours such as aggression, difficulty in adapting, difficulty in forming social relationships, conflicts with oneself and with others, selfishness, and the inability to control oneself.…”
Section: Introductionmentioning
confidence: 99%
“…Goodboy and Frisby (2014) found that students with an unrealistic belief in academic entitlement engage in severe oppositional behaviors and are highly critical of others. While, Kurtyilmaz (2019) explained that entitlement is one of the most critical issues that impact students' academic performance and promote their engagement in undesirable behaviors such as anger, disrespect, and aggression through educational situations.…”
Section: Introductionmentioning
confidence: 99%